"Just a Typical Teenager": The Social Ecology of "Normal Adolescence"—Insights from Diabetes Care. Issue 1 (12th December 2012) - Allen, Davina
<x xml:space="preserve">Abstract</x> In Western society "normal adolescence" is understood to be a biologically driven phase characterized by emotional turmoil and irrational behavior. Despite being discredited within academic literature this discourse persists both in formal theory and everyday use. Drawing on the case of diabetes care, I argue that the discourse of "normal adolescence" derives its power from its value as a vocabulary of motive through which to navigate the contradictions inherent in the social order at this stage of the life‐course. While helping us to comprehend sociologically the ecological niche in which "normal adolescence" is sustained, this analysis raises questions about the persistence of this discourse for social action.